Nutritional knowledge, attitudes, and practices regarding prevention of breast cancer among the female population of Surat district - Pruthvi Parekh; Arti Muley; Srujana Medithi (Discover Social Science and Health)
Abstract Breast cancer incidences in women are rising, emphasizing the importance of its prevention. Adequate nutrition may have a promising role as a preventative strategy. The cross-sectional study aimed to assess the nutritional knowledge, attitudes, and practices (KAP) to prevent breast cancer among 101 women aged 20–40 years residing in Surat and to assess the consumption pattern of antioxidant-rich foods among them. A descriptive questionnaire with references from the literature review was used. A few questions were modified as required for the survey to assess the level of KAP. A pretested questionnaire was used to gather information on demographic variables using a convenience sampling technique. The KAP scores were generated using a questionnaire with seven questions for knowledge; five attitude-related questions and ten questions for practice. Written informed consent was obtained from participants. Descriptive statistics and Chi-square tests were computed using SPSS software (version 28). The mean knowledge score of the participants was 95.17; the mean attitudes score was 8.66; and the mean practice score was 16.08. A significant association was found between attitude score and occupation (p = 0.004). Although the knowledge about antioxidant-rich foods consumption was found to be good, the participants lacked adequate consumption of antioxidant-rich foods. Thus, the findings direct toward good awareness among women regarding breast cancer, which can be used in developing nutrition education programs to bring about behavior change in the dietary practices of the women.